2013
DOI: 10.1002/jmri.24541
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dynamic contrast‐enhanced MRI perfusion parameters with angiogenesis and biologic aggressiveness of rectal cancer: Preliminary results

Abstract: These preliminary results suggest that the determination of kep of high K(trans) area permits the noninvasive estimation of tumor angiogenesis in rectal cancer and that DCE-MRI parameters can be used as imaging biomarkers to predict the biologic aggressiveness of the tumor and patient prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 28 publications
7
57
2
2
Order By: Relevance
“…This result was consistent with the previous study[7]. This differed from other studies: negative correlation between K trans and MVD[9] and no association [6,8,19] (Table5).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result was consistent with the previous study[7]. This differed from other studies: negative correlation between K trans and MVD[9] and no association [6,8,19] (Table5).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have attempted to demonstrate correlation between DCE MRI perfusion parameters and angiogenic factors[610], with variable results. The only study regarding breast DCE MRI demonstrated positive correlation between K trans , k ep and MVD in benign and malignant profiles of breast disease[7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, tumor K trans values have recently been shown to be lower in N1 patients compared with N0 patients. 29 To our knowledge, associations between DSC-MRI and histopathologic data have not been reported in rectal cancer patients. However, a recent study by Goh et al showed that primary colorectal tumor blood flow measured by perfusion computed tomography (CT) was significantly lower in patients with metastatic relapse compared with disease-free patients.…”
Section: Discussionmentioning
confidence: 81%
“…This result is in agreement with that of a recent study showing a significantly higher mean k ep in T1 stage tumors compared with T2-4 stage tumors. 29 A difference was found between the two readers when evaluating the association between histopathologic data and the DCE-and DSC-MRI derived parameters. This may be caused by a lower interobserver agreement in T1-and T2-stage tumor volumes, compared with T3-and T4-stage tumor volumes.…”
Section: Discussionmentioning
confidence: 98%